Elasticity of single-crystal NaCl under high-pressure: simultaneous measurement of x-ray inelastic scattering and diffraction. Issue 4 (1st October 2020) - Fukui, Hiroshi; Yoneda, Akira; Kamada, Seiji; Uchiyama, Hiroshi; Tsutsui, Satoshi; Hirao, Naohisa; Baron, Alfred Q. R.
ABSTRACT: Elastic stiffness constants, C ij s, of single crystal of NaCl B1 phase have been determined at pressure up to 20 GPa using inelastic x-ray scattering to measure elastic wave velocities and x-ray diffraction to measure densities in the same experimental setup. The Voigt-Reuss-Hill average velocities calculated from the present Cij s are in good agreement with previous ultrasonic measurements of polycrystalline samples. Absolute pressures based on the present elastic constants and densities are proposed. In order to fit our results an equation of state with at least three parameters (an addition to a reference volume), such as the fourth-order form of Birch–Murnaghan equation or the higher order form of Vinet equation, is required, as fewer parameters do not reproduce the observed pressure dependence of the volume and bulk modulus.